The Perpetual Peace Puzzle: Kant on persons and states - Holland, Ben (Sage, 2017)
Kant described the state as a ‘moral person’, and did so when dealing with international relations. For all the interest in his contribution to the theory of global politics, the locution according to which Kant characterized the state has received very little attention. When notice has been taken of it, the moral personality of the state has moved arguments in opposing directions. On one recent reading, when Kant called the state a moral person he intended to indicate that it possessed certain duties to itself and to others, for the sake of which it could be coerced to leave the international state of nature. On another, the juridical compulsion of states to join a state of nations or world republic is categorically ruled out because this would impair their moral personality. Both cannot be right. In this paper, I analyze Kant’s notion of moral personhood, contextualizing it within his wider philosophical concerns. On the basis of this groundwork I put forward an argument about Kant’s theory of the moral person of the state which allows me to show how he in fact was able coherently to incorporate two seemingly contradictory arguments about the state as an international actor in a single argument, and present this as my solution to what I call the Perpetual Peace Puzzle.